Enterprise Architecture for the Wedding Shoes Industry - Mulyadi, Grace Devina; Indrajit, Richardus Eko; Dazki, Erick (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Along with the times, especially during this pandemic, the need for the use of the internet, social media, and other digital technologies has become a major lifestyle in every community. This need directly or indirectly creates dependence in every aspect of modern human life. Therefore, it is undeniable that this can be a positive potential if business actors can make good use of it because information technology can change conventional business processes to become easier, more effective and efficient. However, in addition to creating convenience, information technology can cause obstacles for business actors if it is not used properly. Business architecture analysis is one way to assess what business activities need and develop. This journal presents business recommendations for the wedding shoe industry.